If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10G + 1 = 2k + (7X + Y) Reorder the terms: 1 + 10G = 2k + (7X + Y) Remove parenthesis around (7X + Y) 1 + 10G = 2k + 7X + Y Reorder the terms: 1 + 10G = 7X + Y + 2k Solving 1 + 10G = 7X + Y + 2k Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 10G = 7X + Y + -1 + 2k Combine like terms: 1 + -1 = 0 0 + 10G = 7X + Y + -1 + 2k 10G = 7X + Y + -1 + 2k Reorder the terms: 10G = -1 + 7X + Y + 2k Divide each side by '10'. G = -0.1 + 0.7X + 0.1Y + 0.2k Simplifying G = -0.1 + 0.7X + 0.1Y + 0.2k
| 5r+5-r-5= | | -3.8y=-24 | | 3(3+4)=3x+4 | | 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) | | 4w-1+9w= | | 5x+17+7x-29=90 | | 5x+5=5y | | 120+-4.5=120 | | 2ax^2-4(a+1)x+4a+1=0 | | 4x^4-4x^3-17x^2-19x-6=0 | | 5x+4-8=18 | | 3n^2=-4n-1 | | 5(3k+2)=40 | | 6x-5+2x+43=90 | | 3+2(x+2)=15 | | 3(2y+1)=39 | | 2x+8=x+11 | | X=-0.5x+3 | | -7(2t+8)=-126 | | r+(-016)=0.37 | | 5(f-1)=-25 | | (7a^3-2a^2-4a+9)+(3a+6)-(-a^2-a+3)= | | 14x+18y=63 | | -9(T-2)-(t+3)=2 | | x+44=4x+17 | | 2(3x+4)=2x+1 | | 8(s-7)=-92 | | 3x-4=x-10 |